Impact of 4-week of a restricted Mediterranean diet on taste perception, anthropometric, and blood parameters in subjects with severe obesity - Cattaneo, Camilla; Mambrini, Sara Paola; Gilardini, Luisa; Scacchi, Massimo; Pagliarini, Ella; Bertoli, Simona (Frontiers in Nutrition, 2023)
The study of taste functionality and its relation to human health is receiving growing attention. Obesity has been reported to cause alterations in sensory perception regarding system functionality and preferences. However, a small body of research addresses tastes perception and its modification with the achievement of body mass reduction through surgical intervention. Much fewer efforts have been made to evaluate the impact of mild restrictive nutritional intervention on gustatory functions. Thus, the objectives of this study were to determine if a dietary intervention of 4 weeks following a restricted balanced Mediterranean diet would affect the sweet and salty taste thresholds of subjects with severe obesity and could influence their anthropometric and blood parameters. Fifty-one patients with severe obesity (F: 31; age: 43.7 ± 12.5; BMI = 47.6±1.0) were enrolled in the study. The recognition threshold for sweet and salty taste and anthropometric and blood parameters were assessed before and after the 4-week weight loss program. The Mediterranean diet has proven to be an effective treatment, significantly improving all anthropometric and blood parameters (p < 0.05) after 4 weeks of intervention. Moreover, the hypo-sodium treatment associated with the diet significantly improved the salty threshold (p < 0.001). No changes were detected for the sweet threshold. Collectively, these data highlight that dietary treatment might impact taste perception differently. Therefore, a taste-oriented nutritional intervention could represent a novel approach to developing more individualized, taste-oriented follow-up interventions to maintain sustainable and long-term weight loss.